Revitalisasi Branding Lokal Melalui Strategi Co-Creation: Studi Kasus Kopi Suling Khas Toraja dalam Menembus Pasar Urban - Zulfan Zulkarnaen Z; Agung Winarno (Politeknik Kampar, 2025)
Local products such as Kopi Suling Khas Toraja have high cultural and economic potential, but face major challenges in penetrating the modern and competitive urban market. This study aims to examine how co-creation strategies can be used as an approach to revitalize local branding and increase the competitiveness of traditional products in the urban market. The study uses a qualitative approach with a literature study method, examining the concepts of local branding, co-creation, and urban market penetration strategies through the latest library sources. The results of the study show that co-creation, which involves consumers, local communities, and creative actors in the value creation process, can increase consumer emotional involvement and strengthen brand identity.